Efficiency enhancement of perovskite solar cell by modifying the TiO2 with Ag/TiO2 core–shell nanowires. (4th September 2019) - Liu, Yunyan; Li, Shutao; Wang, Shuo; Zhao, Dong; Wang, Rendong; Sun, Meiling; Xiu, Junshan
Abstract : Different ratio incorporation of Ag/TiO2 core–shell nanowires (ATCSN) into TiO2 as an electron transport layer of perovskite solar cells (PSCs) is studied. This structure can prevent the formation of silver halides between perovskite and silver nanowire. It is found that because of the effective improvement of light absorption and separation of photo‐generated electron–hole pairs, the introduction of ATCSN leads to increase of short current density and photoelectric conversion efficiency (PCE) of PSCs. 20 mg incorporation of ATCSN PSCs exhibits the best performance of PCE and a 17.7% increase is achieved compared to the control sample.